Mumps outbreak in an urban community of Western Maharashtra: a case series - Mohan, Ajith; Kaul, Somesh; Modi, Mitesh; Prashant (International Journal Of Community Medicine And Public Health, 2025)
A mumps outbreak was reported in a residential colony in Pune, Maharashtra, starting in September 2023, with the index case being a 12-year-old girl from school A, who presented with fever and parotitis and had no history of measles, mumps, and rubella (MMR) vaccination. A total of 10 cases were identified, including one serologically confirmed case and nine epidemiologically linked cases, traced to two schools (A and B), with likely transmission occurring in communal areas like playgrounds. Only 30% of the cases had documented MMR vaccination, highlighting gaps in immunization coverage. Public health measures, including isolating symptomatic individuals and educating residents on mumps transmission, prevention, and symptoms, were implemented to control the outbreak. This case series underscores the resurgence of mumps in a partially vaccinated urban community, emphasizing the need for improved MMR vaccination coverage and inclusion of the MMR vaccine in India’s Universal Immunization Program to prevent future outbreaks.